2020
DOI: 10.1186/s12903-020-01267-4
|View full text |Cite
|
Sign up to set email alerts
|

Candida prevalence and oral hygiene due to orthodontic therapy with conventional brackets

Abstract: Background Conventional brackets are often used during orthodontic therapy of patients with malocclusion. The complex construction of such brackets greatly inhibits oral hygiene, which predisposes to increased carriage of microbiota. Orthodontic brackets could act as reservoir of yeast and predispose to oral candidosis. The aim of this study was to assess Candida prevalence and the role of oral hygiene during fixed appliance therapy. A further aim was to characterize the isolated yeasts according to their abil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…In their work, Arslan et al characterized by culture methods Candida species found in 58% of a group of adolescents with fixed orthodontic appliances: C. albicans was predominant (73.8%), followed by C. tropicalis, C. krusei and C. kefyr (7.14%), and C.parapsilosis (4.76%) [ 63 ]. Similar rates were reported by Grzegocka et al [ 65 ] who analyzed Candida spp . from oral rinses and suprangingival plaque in 17 orthodontic subjects (mean age 17 ± 7 years) founding 59% of Candida carriers among them, and a strongly correlation with the massive presence of plaque.…”
Section: Protozoas Fungi and Other Bacterial Species In Orthodontsupporting
confidence: 89%
“…In their work, Arslan et al characterized by culture methods Candida species found in 58% of a group of adolescents with fixed orthodontic appliances: C. albicans was predominant (73.8%), followed by C. tropicalis, C. krusei and C. kefyr (7.14%), and C.parapsilosis (4.76%) [ 63 ]. Similar rates were reported by Grzegocka et al [ 65 ] who analyzed Candida spp . from oral rinses and suprangingival plaque in 17 orthodontic subjects (mean age 17 ± 7 years) founding 59% of Candida carriers among them, and a strongly correlation with the massive presence of plaque.…”
Section: Protozoas Fungi and Other Bacterial Species In Orthodontsupporting
confidence: 89%
“…Topaloglu et al 11 observaron un aumento en los pacientes portadores de Candida en el seguimiento a los 6 meses de tratamiento, el número de pacientes que completaron el estudio fue muy bajo. En concordancia con este estudio, Grzegocka et al 33 describieron que el tratamiento ortodóntico promovió la colonización de las levaduras con variaciones durante el tiempo estudiado, con un bajo número de pacientes portadores. Los resultados de este estudio en coincidencia con los trabajos mencionados reflejarían la habilidad de las bacterias cariogénicas frente a Candida para competir en la supervivencia en la placa bacteriana.…”
Section: Discussionunclassified
“…Fixed orthodontic appliances with increasing accuracy and reliability are used in daily clinical practice. However, how to effectively avoid enamel demineralization and maintain good levels of oral hygiene during treatment is still a problem to be overcome [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%